Eco’s Lingua Edenica and "other languages" - Šimić, Krešimir (Bogoslovni vestnik, 2023)
The paper introduces a close reading of Eco’s article “Generazione di messaggi estetici in una lingua edenica” (1971), in which he fictionalized the biblical story from Gen 2 to show that the aesthetic use of language generates internal contradictions (self-contradictions), as well as that any such contradiction at the level of expression/form also entails a contradiction at the level of content. Furthermore, the basic postulates of Eco’s semiotic theory revolving around the sign-function are discussed, followed by outlining certain theological-semiotics of language based on the text from the second chapter of the Acts of the Apostles (descent of the Spirit). It is based on an original sign – which is not, as with Eco, a sign associated with another sign (interpretant) within a sign system (code) nor a “dynamic object,” but it is the Mystical Body. The paper concludes by arguing that it is this very Body, and not the poetic invention, that generates “other languages” (??????? ????????) and consequently a communion, which is not multiethnic nor multilingual, but a Catholic community.
Keywords: “other languages”; „drugi jeziki“; Eco, Umberto; mistično telo; mystical body; semiotic; semiotika; sign; znak